The imagined life : a novel - Porter, Andrew, 1972- (Alfred A. Knopf, 2025)
"Steven Mills has reached a crossroads. His wife and son have left, and they may not return. Which leaves him determined to find out what happened to his own father, a brilliant, charismatic professor who disappeared in 1984 when Steve was twelve, on a wave of ignominy. As Steve drives up the coast of California, seeking out his father's friends, family members, and former colleagues, the novel offers us tantalizing glimpses into Steve's childhood-his parents' legendary pool parties, the black-and-white films on the backyard projector, secrets shared with his closest friend. Each conversation in the present reveals another layer of his father's past, another insight into his disappearance. Yet with every revelation, his father becomes more difficult to recognize. And, with every insight, Steve must confront truths about his own life. Rich in atmosphere, and with a stunningly sure-footed emotional compass, The Imagined Life is a probing, nostalgic novel about the impossibility of understanding one's parents, about first loves and failures, about lost innocence, about the unbreakable bonds between a father and a son"--